Developing local hospitals for public health excellence - Thienthong K. (2023)
The current study investigated the factors affecting the success of local hospital operations in promoting public health excellence in Thailand. A mixed method approach with focus groups and questionnaires was utilized. The study also depended on descriptive statistics and hierarchical regression analysis. According to the findings, public health providers agreed that the main factors leading to the success of local hospital operations were participation with people in the community, respect, and policy development. Other aspects included the use of devices, tools, medicine or medical supplies, training, and project organization. Meanwhile, the service recipients held the view that any suggestion of information, knowledge, or capability of personnel has an influence on operational guidelines. However, success at higher levels must rely on two things: 1) the location of a local hospital and 2) analysis of the guidelines for developing the services of local hospitals for promoting public health in the future. The study also relied on content analysis. According to the findings, appropriate operating guidelines for local hospitals would comprise policy development for promoting public health, participation by people in the community, and public services by the hospital, including training to increase the potential of personnel and project organization involving health promotion.